PENGARUH RETURN ON ASSETS (ROA) DAN DEBT TO ASSETS RATIO (DAR) TERHADAP TAX AVOIDANCE DENGAN GLOBAL MINIMUM TAX SEBAGAI VARIABEL MODERASI DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL KONTROL(Studi Empiris pada Perusahaan Multinasional di BEI Periode 2021–2025) - Nadia Nostiva Azra; Riza Reni Yenti (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2026)
This study aims to examine the effect of Return on Assets (ROA) and Debt to Assets Ratio (DAR) on tax avoidance, as well as the moderating role of the Global Minimum Tax (GMT) in multinational companies listed on the Main Board of the Indonesia Stock Exchange during the 2021–2025 period. This study employs a quantitative approach using panel data regression analysis. The sample consists of multinational companies selected through purposive sampling, and the data are analyzed using the Fixed Effect Model (FEM). Tax avoidance is measured using the Effective Tax Rate (ETR), while firm size is included as a control variable. The results indicate that Return on Assets (ROA) has a significant negative effect on tax avoidance, whereas Debt to Assets Ratio (DAR) has a significant positive effect on tax avoidance. Furthermore, the Global Minimum Tax (GMT) weakens the effect of Return on Assets (ROA) on tax avoidance and strengthens the effect of Debt to Assets Ratio (DAR) on tax avoidance. These findings provide empirical evidence that the implementation of the Global Minimum Tax (GMT) has influenced the relationship between corporate financial characteristics and tax avoidance among multinational companies in Indonesia.